Farrerol Alleviates Myocardial Ischemia/Reperfusion Injury by Targeting Macrophages and NLRP3 - Zhou, Lin; Yang, Shuhui; Zou, Xiaoming (Frontiers in Pharmacology, 2022)
Myocardial ischemia/reperfusion (I/R) injury is associated with high mortality and morbidity, and has no curative treatment. Farrerol (FA), an active compound extracted from rhododendron, has antibacterial, anti-inflammatory, and antioxidant activities. However, the effect and mechanism of FA in I/R injury remain unclear. Here, we found that FA alleviated myocardial I/R in vivo, decreased the secretion of myocardial injury factors (CK-MB, LDH, troponin-1, and NT-proBNP), inhibited the release of inflammatory factors (IL-1β, IL-6, and TNF-α), and decreased the expression of apoptosis-associated proteins (cleaved caspase-3, Bax, and Bcl-2). However, inhibiting the autophagic pathway or knocking out the Nrf2 gene did not eliminate the myocardial protective effect of FA. Interestingly, macrophage clearance and Nlrp3 deficiency effectively blocked the myocardial protective effect of FA. In addition, FA suppressed NLRP3 inflammasome activation by interfering with NLRP3 and NEK7. In conclusion, these results support drug-targeted macrophage therapy for myocardial I/R and indicate that FA may be used as an immunomodulator in clinical therapy for myocardial I/R.